2021
DOI: 10.1155/2021/5933652
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Medical Entity Recognition Model Based on Character and Word Vector Fusion

Abstract: The medical information carried in electronic medical records has high clinical research value, and medical named entity recognition is the key to extracting valuable information from large-scale medical texts. At present, most of the studies on Chinese medical named entity recognition are based on character vector model or word vector model. Owing to the complexity and specificity of Chinese text, the existing methods may fail to achieve good performance. In this study, we propose a Chinese medical named enti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Experimental results have demonstrated that the model, which fuses character and word information, exhibits stronger entity recognition capabilities. Zhang et al [17] proposed a method that represents Chinese text as both character vectors and word vectors, which are integrated into a feature model. This model effectively addresses the issues of missing information in character vectors and inaccurate division in word vectors.…”
Section: Related Workmentioning
confidence: 99%
“…Experimental results have demonstrated that the model, which fuses character and word information, exhibits stronger entity recognition capabilities. Zhang et al [17] proposed a method that represents Chinese text as both character vectors and word vectors, which are integrated into a feature model. This model effectively addresses the issues of missing information in character vectors and inaccurate division in word vectors.…”
Section: Related Workmentioning
confidence: 99%
“…The dictionary-based approaches face pretty much the same problem in covering all related entities, which causes poor recognition performance [ 31 ]. Machine learning-based approach at earlier stage takes a naïve resolution by simply classifying each word independently [ 32 ]. The main problem with this resolution is it assumes that named entity labels are independent which is not the case.…”
Section: Related Workmentioning
confidence: 99%